MOTIVASI BERPENGARUH TERHADAP KEPATUHAN PERAWAT DALAM PELAKSANAAN PROTOKOL KESEHATAN COVID-19 DI RUMAH SAKIT SWASTA DI BANJARMASIN - Amaliah, Noor; Azidin, Yustan; Fitriani, Siti (JURNAL KEPERAWATAN SUAKA INSAN (JKSI), 2023)
Abstract All health workers, especially nurses, must comply with the Covid prevention health protocol 19 especially hand washing and the use of PPE. One important factor influencing nurse compliance is the nurse's motivation. This study aims to determine the relationship between motivation and nurse compliance in implementing the Covid-19 health protocol. This study used a cross-sectional design. The population was all nursing staff in the Covid 19 isolation room of a private hospital in Banjarmasin, totaling 30 people, taken using a saturated sampling technique. Data analysis was using Spearman Rank. The results showed that there was a relationship between motivation and nurse compliance in implementing the Covid-19 health protocol at Banjarmasin Private Hospital with a value of ? = 0.000 and the strength of the relationship was very strong (r = 0.996). Socialization or training regarding the implementation of the Covid-19 health protocol needs to be carried out for all nurses working in the Covid-19 isolation room. Keywords: Motivation, Compliance, Covid-19 Health Protocol.